2009
DOI: 10.1093/glycob/cwp024
|View full text |Cite
|
Sign up to set email alerts
|

Negative-ion MALDI-QIT-TOFMSn for structural determination of fucosylated and sialylated oligosaccharides labeled with a pyrene derivative

Abstract: Oligosaccharides have many isomers and MALDI-QIT-TOFMS(n) analysis is effective for determining their structures. However, it is difficult to elucidate in detail the structures of fucosylated and/or sialylated oligosaccharides that are known to be disease markers because fucose and sialic acid residues are easily released. We have introduced a technique of labeling oligosaccharides with a pyrene derivative prior to negative-ion MALDI-QIT-TOFMS(n), and we have established a reliable method using this technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 18 publications
0
36
0
2
Order By: Relevance
“…The total number of identified N-linked glycans could be increased by about 10% [48] . Amano and coworkers reported the derivatization of oligosaccharides with pyrene butanoic acid hydrazide (PBH); as little as 10 fmol of oligosaccharides were sufficiently detected by negative-ion MALDI-TOF-MS n [49] . By the further derivatization of neutral oligosaccharide fraction from milk of a woman, total 22 oligosaccharides were identified, among which 21 had novel structures [50] .…”
Section: Derivatization Of Glycan/glycopeptidementioning
confidence: 99%
“…The total number of identified N-linked glycans could be increased by about 10% [48] . Amano and coworkers reported the derivatization of oligosaccharides with pyrene butanoic acid hydrazide (PBH); as little as 10 fmol of oligosaccharides were sufficiently detected by negative-ion MALDI-TOF-MS n [49] . By the further derivatization of neutral oligosaccharide fraction from milk of a woman, total 22 oligosaccharides were identified, among which 21 had novel structures [50] .…”
Section: Derivatization Of Glycan/glycopeptidementioning
confidence: 99%
“…For example, fucose residues are preferentially detached from the glycan chain during CID and therefore cannot be localized by positive-ion CID. 17) Moreover, monosaccharide rearrangements may occur in the dissociation of (protonated) glycoconjugates, making MS/MS-based structural elucidation more di cult. 18,19) Recent studies have revealed that the use of the negative-ion mode in the analysis of glycoconjugates o ers distinct advantages with respect to structural elucidation.…”
Section: Introductionmentioning
confidence: 99%
“…The structural determination of glycans based on MS n has also been performed in positive-ion mode because glycans usually ionize as [M+Na] + or [M+K] + . Recently, CID of negatively charged ions has proved to be effective for the structural determination of glycans [26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we have focused on the analysis of both neutral and acidic glycans in negative-ion mode, rather than positive-ion mode, because negative-ion CID of glycans derivatized with pyrene generate unique product ions for structural determination [29,30]. In general, negative-ion formation from neutral glycan is difficult, showing no or low ion yields.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation